Search for the doubly heavy baryons and decaying to and *We acknowledge support from CERN and from the national agencies: CAPES, CNPq, FAPERJ and FINEP (Brazil); MOST and NSFC (China); CNRS/IN2P3 (France); BMBF, DFG and MPG (Germany); INFN (Italy); NWO (Netherlands); MNiSW and NCN (Poland); MEN/IFA (Romania); MSHE (Russia); MICINN (Spain); SNSF and SER (Switzerland); NASU (Ukraine); STFC (United Kingdom); DOE NP and NSF (USA). We acknowledge the computing resources that are provided by CERN, IN2P3 (France), KIT and DESY (Germany), INFN (Italy), SURF (Netherlands), PIC (Spain), GridPP (United Kingdom), RRCKI and Yandex LLC (Russia), CSCS (Switzerland), IFIN-HH (Romania), CBPF (Brazil), PL-GRID (Poland) and NERSC (USA). We are indebted to the communities behind the multiple open-source software packages on which we depend. Individual groups or members have received support from ARC and ARDC (Australia); AvH Foundation (Germany); EPLANET, Marie Skłodowska-Curie Actions and ERC (European Union); A*MIDEX, ANR, Labex P2IO and OCEVU, and Région Auvergne-Rhône-Alpes (France); Key Research Program of Frontier Sciences of CAS, CAS PIFI, CAS CCEPP, Fundamental Research Funds for the Central Universities, and Sci. Tech. Program of Guangzhou (China); RFBR, RSF and Yandex LLC (Russia); GVA, XuntaGal and GENCAT (Spain); the Leverhulme Trust, the Royal Society and UKRI (United Kingdom). (September 2021) - Aaij, R.; Abellán Beteta, C.; Ackernley, T.; Adeva, B.; Adinolfi, M.; Afsharnia, H.; Aidala, C.A.; Aiola, S.; Ajaltouni, Z.; Akar, S.; Albrecht, J.; Alessio, F.; et al.
Abstract: The first search for the doubly heavy baryon and a search for the baryon are performed using collision data collected via the experiment from 2016 to 2018 at a centre-of-mass energy of, corresponding to an integrated luminosity of 5.2 . The baryons are reconstructed via their decays to and . No significant excess is found for invariant masses between 6700 and 7300, in a rapidity range from 2.0 to 4.5 and a transverse momentum range from 2 to 20 . Upper limits are set on the ratio of the and production cross-section times the branching fraction to ( ) relative to that of the ( ) baryon, for different lifetime hypotheses, at 95% confidence level. The upper limits range from to for the ( ) decay, and from to for the ( ) decay, depending on the considered mass and lifetime of the ( ) baryon.